La Revolución Rusa en el país de los zares. Impactos y problemas - Sgrazzutti, Jorge (2017)
Fil: Fil: Sgrazzutti, Jorge. Universidad Nacional de Rosario; Argentina Fil: Oliva, Antonio. Universidad Nacional de Rosario; Argentina